DAF-16/FOXO Transcription Factor in Aging and Longevity - Sun, Xiaojuan; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Pharmacology, 2017)
Aging is associated with age-related diseases and an increase susceptibility of cancer. Dissecting the molecular mechanisms that underlie aging and longevity would contribute to implications for preventing and treating the age-dependent diseases or cancers. Multiple signaling pathways such as the insulin/IGF-1 signaling pathway, TOR signaling, AMPK pathway, JNK pathway and germline signaling have been found to be involved in aging and longevity. And DAF-16/FOXO, as a key transcription factor, could integrate different signals from these pathways to modulate aging and longevity via shuttling from cytoplasm to nucleus. Hence, understanding how DAF-16/FOXO functions will be pivotal to illustrate the processes of aging and longevity. Here, we summarized how DAF-16/FOXO receives signals from these pathways to affect aging and longevity. We also briefly discussed the transcriptional regulation and posttranslational modifications of DAF-16/FOXO, its co-factors as well as its potential downstream targets participating in lifespan according to the published data in C.elegans and in mammals, and in most cases, we may focus on the studies in C.elegans which has been considered to be a very good animal model for longevity research.